The efficacy of recycled concrete aggregate for removal phosphorus in synthetic wastewater with different pH value - Adnan, Suraya Hani; Abd Roni, Norwardatun; Hamidon, Nuramidah; Tuan Ismail, Tuan Noor Hasanah (UTHM, 2020)
Phosphorus (P) is the main nutrient element for plant growth in the natural water system. However, unnecessary phosphorus loads in water bodies from industrial, agricultural and household wastes may cause the overgrowth of aquatic plants or algae which accelerates the depletion of dissolved oxygen (DO) in water, thereby leading to serious eutrophication problems. Nevertheless, existing conventional wastewater treatment systems for removing phosphorus are expensive and complex. Recycled concrete aggregate (RCA) may be an alternative solution for phosphorus removal. It can reduce pollution and landfill disposal by converting construction waste into valuable products. This study aims to investigate the percentage of phosphorus removal using three different sizes of RCA with different pH of synthetic wastewater. A total of four vertical laboratory-scale RCA filters were designed with four different concentrations of synthetic wastewater which is pH3, pH7, pH9 and distilled water were prepared. The pH and the percentage of phosphorus removal (%) were tested and analysed on both untreated and treated sample. RCA was analysed using Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray spectroscopy (EDX) to determine its chemical composition. The results show that RCA has a high content of aluminium, calcium and magnesium that enhances phosphorus adsorption. The pH values are substantially higher for RCA size 5 mm to 10 mm compared to RCA size 10 mm to 15 mm, and 15 mm to 20 mm. Moreover, it was shown that the higher the pH, which is at pH 9 and the smaller size of RCA, the higher the efficiency of phosphorus removal, which is 96% of removal. In conclusion, RCA has the potential to remove phosphorus, particularly in low concentrations of synthetic wastewater and high pH conditions.